A distance protection scheme for HVDC transmission lines based on the Steady-state parameter model. (March 2022) - Zheng, Junchao; Li, Peng; Xu, Kai; Kong, Xiangping; Wang, Chenqing; Lin, Jinjiao; Zhang, Chi
Highlights: During the steady state of the DC line fault, the line model is equivalent to the lumped parameter model. A directional relay based on transient currents is proposed to solve the dead-zone problem. The novel protection does not require powerful computing ability and high sampling frequency. Abstract: To improve the performance of the protection scheme for HVDC lines, a novel distance backup protection scheme is proposed in this paper. First, it is proved that the DC line model can be equivalent to lumped parameter model during the steady-state. Based on the equivalent model, the fault distance can be calculated, and the criterion of the distance relay is implemented. Secondly, a directional relay based on the transient currents is added to solve the dead zone problem of distance protection. Finally, a ± 800 kV HVDC system is built in PSCAD/EMTDC simulation environment to test the performance of the protection. Comprehensive test studies show that the proposed protection scheme can correctly distinguish internal faults from external faults. Besides, the proposed protection has a clear setting principle, low requirements of the calculation amount and sampling rate.